Guía de práctica clínica para el tamizaje de cáncer de mama en el Seguro Social del Perú (EsSalud) - Salvatierra Romero, Guillermo (2024)
Introduction. This article provides an overview of the clinical practice guideline (CPG) for breast cancer screening in the Social Security of Peru (EsSalud). Objective. To offer evidence-based clinical recommendations for breast cancer screening within EsSalud. Methods. The CPG for breast cancer screening was developed by establishing a guideline development group (local GDG) consisting of medical specialists and methodologists. The local GDG formulated 5 clinical questions to be answered by this CPG. Systematic searches of systematic reviews and, when it was considered pertinent, primary studies were conducted in Pubmed and Cochrane CENTRAL during 2022. The evidence to answer each of the posed clinical questions was selected. The quality of the evidence was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic work meetings, the local GDG used the GRADE methodology to review the evidence and formulate the recommendations, points of good clinical practice, and the flowchart of screening Finally, the CPG was approved with Resolution No. 68-IETSI-ESSALUD-2022. Results. The CPG examined 5 clinical questions related to physical examination and diagnostic imaging for breast cancer screening. This led to the development of 8 recommendations (2 strong and 6 conditional), 7 best practice points, and 1 flowchart. Conclusion. This article outlines the methodology and evidence-based findings of the CPG for breast cancer screening at EsSalud.